WDM-Based 160 Gbps Radio Over Fiber System With the Application of Dispersion Compensation Fiber and Fiber Bragg Grating - Kumar, Suresh; Sharma, Sonia; Dahiya, Sandeep (Frontiers in Physics, 2021)
The demand for data transmission is rising expensively for the applications of biomedical sensors data, multimedia technologies and ultra-high definition online video streaming. Such applications require larger bandwidth with minimum latency and seamless service delivery. Radio–over-Fiber (RoF) integrated with Wavelength Division Multiplexing (WDM) technology is being considered one of the promising technology. However, the integration of optical fiber and wireless communication also generates nonlinear effects as and when the number of users increased. That results in introduction of signal noise, unwanted frequencies, low quality of signals and increased latency. In this paper, a 16 channel160 Gbps data rate WDM based RoF system has been simulated and evaluated for optimum performance at variable input power level from 5dbm to -15dbm with the application of Dispersion Compensation Fiber (DCF) and Fiber Bragg Grating (FBG) with channel spacing of 50GHz and 100GHz. The performance of the system is evaluated with existing WDM-RoF system. The performance metrics parameters chosen for evaluation are Bit Error Rate (BER), Quality Factor (Q-Factor) and Eye diagrams and simulated on Opti-system Simulator. The optimum performance has been observed at a power level of -5dbm for all these selected evaluation parameters. It has also been observed that for channel spacing of 100GHz, the network performed better in comparison to 50 GHz.